The biochemistry of antigen presentation - Springer, S; Springer, Sebastian Hartmut (1996)
﻿ This thesis describes studies on the binding of peptides to the murine major histocompatibility complex (MHC) class I molecule H-2Db (Db). The expression of the recombinant soluble Db molecule in Chinese hamster ovary cells and its subsequent purification by nickel affinity chromatography, gel filtration, and preparative native isoelectric focusing are reported. The product is the correct molecule, homogeneous, a dimer of dimers, and free of endogenous peptide. A novel binding assay based on the enhancement of natural tryptophan fluorescence by the binding of peptide is introduced. This assay is used to determine melting curves of the empty and peptide-loaded protein, and to measure association rate constants by stopped-flow fluorescence spectroscopy. Radioligand binding measurements of equilibrium as well as association and dissociation rate constants and their temperature dependence are reported. In agreement with earlier observations, the ratio of association and dissociation rate constants is much larger than the equilibrium association constant. Fluorescence anisotropy decay spectroscopy gives evidence for conformational alterations in the Db molecule upon peptide binding. The data, possible errors and ways to avoid them, and mathematical models of binding are discussed to obtain an overall picture of the binding process.